Mental Health in Children in the Context of COVID-19: Focus on Discharged Children - Zhang, Anyi; Shi, Le; Yan, Wei; Xiao, Han; Bao, Yanping; Wang, Zhe; Deng, Jiahui; Ravindran, Arun; Yuan, Kai; Mei, Hong; Shi, Jie; Liu, Zhisheng; et al. (Frontiers in Psychiatry, 2021)
Introduction: To date, the mental health consequences of children hospitalized with COVID-19 remain unclear. We aimed to assess mental health status in children in the context of COVID-19, with a focus on discharged children. Methods: We recruited discharged children who recovered from COVID-19 and healthy controls between July and September 2020 in Wuhan Children’s Hospital. Posttraumatic stress disorder (PTSD), anxiety, depression, and sleep problems were assessed in these children using questionnaires. Univariable and multivariable logistic and linear regressions were conducted to identify risk factors. Results: Totally, there were 152 children (61 discharged children and 91 healthy controls) aged 7-18 years old in our study. An increasing trend in the prevalence of PTSD, anxiety, and depression was observed in the discharged children compared with healthy controls (PTSD: 8.20% vs. 2.20%, anxiety: 22.95% vs. 13.19%; depression: 47.54% vs. 32.97%). Discharged children tended to report more depressive symptoms (β = 0.39) and less sleep problems (β = -0.37). Discharged children who lived in nuclear families and had longer hospital stays were more likely to report depression (odds ratio [OR] = 3.68 and 1.14, respectively). Anxiety symptoms and the severity of sleep problems of discharged children were positively associated with caregivers’ depression and PTSD symptoms (OR = 21.88 and 31.09, respectively). Conclusion: In conclusion, PTSD, anxiety, and depression symptoms were common among recovered children 4 months after COVID-19 hospitalization. Children from nuclear family and those had longer hospital stays need special attention. In addition, parental mental health had a significant impact on their children’s mental resilience and recovery.